How to track cellular aging of mesenchymal stromal cells? - Wagner, Wolfgang; Bork, Simone; Lepperdinger, Günther; Joussen, Sylvia; Ma, Nan; Strunk, Dirk; Koch, Carmen (Aging, 2010)
Aging | doi:10.18632/aging.100136. Wolfgang Wagner, Simone Bork, Günther Lepperdinger, Sylvia Joussen, Nan Ma, Dirk Strunk, Carmen Koch
Gesehen am 28.09.2023